Comparison of Some Soil Enzymatic Activities in Luvisol of Conservation and Conventional Tillage in a Model Experiment - Nugroho, Priyo Adi; Prettl, Nándor; Kotroczó, Zsolt; Juhos, Katalin (Journal of Central European Green Innovation, 2022)
The effect of soil tillage operation on soil biological properties has not been extensively studied in Hungary. We investigated some soil biological enzymatic activities (dehydrogenase, β-glucosidase, and phosphatase) of a Luvisol, treated by different tillage, management intensities, i.e., conservation tillage (CT), fully conventional tillage with mouldboard ploughing every year (PT), and moderately conventional tillage with shallow and deep ripping intermittently in every two years (BR). A pot experiment was carried out in climate-controlled growth chamber for six weeks as a model experiment, of using the composite soils (0-20 depth) with the three types of tillage intensity. Our finding suggested, that adding of the crop residues might increase the soil organic matter content, that is reflected by the high concentration of labile carbon in the CT soil. The greater intensified soil aeration at the conventional tillage operation, contributed to the much higher dehydrogenase activity in the PT and the BR soil. Otherwise, the higher aeration of soil resulted a decreased β-glucosidase activity in the conventional tillage (BR) soil. The high phosphorus availability of soil correlated by the lowest phosphatase enzymatic activity and the improved available P ratio in CT soil, indicating the inhibition of phosphatase activity. The soil biological enzymatic activities was shown to be affected by the presence of different substrates at the three management practices.